Peran Serta Humas PT.Jasa Raharja Perwakilan Medan Dalam Mensosialisasikan Layanan Asuransi Kecelakaan Lalu - Lintas Jalan Dan Penumpang Umum Kepada Masyarakat Kota Medan - dea rahmadiani rahmadiani; Rahmi Syahriza (UIR Press, 2022)
The research method in this research is using a qualitative method with a descriptive approach. To analyze research data, use interactive model data analysis, and then make comparisons to the data that has been collected. From the results of the study, the authors conclude that the contribution of public relations at PT. Jasa Raharja Perwakilan Medan to publish road traffic accident insurance and public transportation services to the people of Medan City has been quite successful, as evidenced by the level of public understanding of social insurance managed by PT. Jasa Raharja Perwakilan Medan. There is also the contribution of public relations that has been given in publishing insurance services to the people of Medan City in the form of improving services, informing, communicating and taking full responsibility both in terms of time, place, and conditions and oriented to the priority of the public interest.